(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to produce a valid, practical, and effective E-LKPD based on guided inquiry using Liveworksheet on the style material of grade IV of SDN Junganyar 2. The type of research used is Research & Development with a 4D development model (Define, Design, Development, Disseminate). The subjects of the study were 27 grade IV students of SDN Junganyar 2 as well as validators who are teaching material experts, learning design experts, and material experts. Data collection techniques include interviews, observations, questionnaires, and tests. Data analysis techniques use quantitative analysis in the form of percentages to assess the validity, practicality, and effectiveness of the product. The results showed that the E-LKPD obtained a percentage of teaching material validation of 86.66%, learning design validation of 91.66%, and material validation of 89.58% with a very valid category. The practicality of the product was demonstrated through teacher observations of 100% and student observations of 96%. The effectiveness of the product was seen from the classical completeness of students of 100% and student questionnaire responses of 94%. This research was limited to the topic of force and was conducted only at one elementary school, namely SDN Junganyar 2. Therefore, further research is recommended to develop E-LKPD on other materials and involve a wider range of research subjects. Thus, E-LKPD is declared valid, practical, and effective for use in learning sciences on force material.